Arquitetura e alometria de espécies arbóreas em uma floresta estacional subtropical - Costa, Malcon do Prado (2014)
The aim of this study was to describe some architectural models and study their behavior in vegetation structure, allometric patterns and their growth dynamics to support management activities and conservation of tree species in seasonal forest of Santa Maria (RS). In the first chapter a descriptive analysis was performed of the species present in the fragment and its architectural models. A list of 53 species of tree flora of a Subtropical feasonal forest in Santa Maria (RS), distributed in 45 genera and 28 families in the local flora gifts inventoried. In the second chapter a study of the species and the behavior of architectural models were performed in the vertical structure of the community. When an association was detected between species and their architectural models with vertical forest strata. The natural disturbances in the architecture of the forest as the formations of gaps provide explanations for the persistence of species with irregular distribution in the vertical structure of the Forest. In the third chapter of the mechanical designs of architectural models have been studied and have been selected among a few variables, which best explain the increase in basal area of individual trees in the remaining. The variables that best explained the increase in basal area of trees were diameter at breast height, crown diameter and salience index, and the architectural models of categorical variable increased the efficiency of regression. The study of vegetation dynamics from the behavior of groups of species of architectural models are promising for planning activities of forest ecosystems.